The effects of trade liberalization with spatial markets - Andreas Kopp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
It is established that with the reduction of trade barriers the number of competitors on the spatial markets involved increases. This increase has short run consequences for price competition. If the trade liberalisation is anticipated by the domestic producers they will respond by changing the locational pattern as well. A unique locational equilibrium is established from the no further entry condition of the process of sequential location of exporters' outlets in the import markets. The entry process stops if no further entrant can locate between the last entrant and any of the suppliers having entered the market before without being undercut in the price game.
Keywords: 330; Räumlicher Wettbewerb; Räumliche Preistheorie; Außenhandelsliberalisierung; Offene Volkswirtschaft; Theorie